Study of effects of oligohydramnios on perinatal outcome - Mashkaria, Aashka M.; Patel, Babulal S.; Shah, Akshay C.; Jani, Shashwat K.; Patel, Vismay B.; Patel, Adwait B.; Mashkaria, Aastha M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Oligohydramnios has got a noteworthy influence on perinatal outcome. Hence, early detection and its timely management will aid in curtailing of perinatal morbidity and mortality and leading to decreased operative interventions. Therefore, the present study is conducted to look for the effects of oligohydramnios. Methods: This comparative study was a prospective observational study conducted at study institution. The women were divided into study and control groups based on AFI (amniotic fluid index), 100 cases were selected in each group. Results: Out of the 200 women, included in the present study, 35% of the patients in the study group had non-reactive non-stress test (NST) while in the control group 7% had it. Caesarean section was performed in 58% of cases in the study group as compared to 30% in the control group. Amongst these, Fetal distress was the most common indication for LSCS (lower segment caesarean section). There were no perinatal deaths in this study. Conclusions: Based on this study it has been observed that, amniotic fluid index of ≤5 cm was commonly associated with increased LSCS rates, intrauterine growth restriction, non-reactive NST, and abnormal Doppler velocimetry studies. Therefore, every case of oligohydramnios requires to be assessed meticulously. Prompt detection; timely management and treating the underlying condition improve outcome.